2019
DOI: 10.1177/1460458219879337
|View full text |Cite
|
Sign up to set email alerts
|

Integrating usability and social cognitive theories with the technology acceptance model to understand young users’ acceptance of a health information portal

Abstract: The past decade has seen the proliferation of health information portals; however, consumer acceptance of the portals has proven difficult and rate of use has been limited. This study developed a consumer acceptance model by integrating usability and social cognitive theories with the technology acceptance model to explain young Internet users’ acceptance of health information portals. Participants (n = 201) completed a self-report questionnaire measuring model constructs after attending a usability testing wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 62 publications
4
59
1
3
Order By: Relevance
“…Hypothesis 6 is also tested as insignificant, for the indirect effect of effort expectancy on purchase intention is not significant (see Table 9). Notably, the effect of effort expectancy differs from the results of prior literature (Dwivedi et al, 2019; Tao, Shao, et al, 2020; Zhou et al, 2010). Previous studies are based on the instance of different markets and the products vary across studies.…”
Section: Discussioncontrasting
confidence: 95%
“…Hypothesis 6 is also tested as insignificant, for the indirect effect of effort expectancy on purchase intention is not significant (see Table 9). Notably, the effect of effort expectancy differs from the results of prior literature (Dwivedi et al, 2019; Tao, Shao, et al, 2020; Zhou et al, 2010). Previous studies are based on the instance of different markets and the products vary across studies.…”
Section: Discussioncontrasting
confidence: 95%
“…This is within the adoption process that also contributes to the facilitation of the implementation effectiveness. The decision and implementation stages concerning the adoption of the innovation (readiness for implementation and executing) are determined by 2 predictors of attitude toward the usage, as indicated in the Technology Acceptance Model [ 40 ] on the perceived usefulness and perceived ease of use. Time of adoption also plays a crucial element in the adoption or resistance of the innovation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interpersonal communication is used to spread word of the mouth concerning the testimonies on innovation usage (eg, network and communication/goals and feedback) and social reinforcement from peers (social system). This is within the adoption process that also contributes to the facilitation of the [40] on the perceived usefulness and perceived ease of use. Time of adoption also plays a crucial element in the adoption or resistance of the innovation [41].…”
Section: Using Cfir and Diffusion Of Innovation Theory (Proposed Bymentioning
confidence: 99%
“…In TAMs, technology acceptance is considered a determinant of technology use. Hence, health care professionals' acceptance of a digital technology can be considered a determinant of its use [26][27][28][29][30]. Although TAMs have been widely used to explain the use of many different technologies, health care research has shown them to be highly suited to analyzing eHealth use.…”
Section: Hypotheses and Modelmentioning
confidence: 99%